IoT based automated entry system with integration of Covid-19 symptom detection - Ruhin, Rubaiyat Alam; Islam, Aminul; Mahi, Tahsin Muhtady (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.